A CFD-based Virtual Test-rig for Rotating Heat Exchangers. (December 2015) - Corsini, Alessandro; Delibra, Giovanni; Di Meo, Giulio; Martini, Mirko; Rispoli, Franco; Santoriello, Andrea
Abstract: Rotating heat exchangers are used in steel industry, air conditioning and thermal power plants to pre-heat air used in steam generators or for waste heat recovery. Here we focus on a rotating heat exchanger on a so-called Ljungström arrangement operated in thermal power plants to pre-heat the air fed to the steam generators. In these devices the heat exchange between two fluids is achieved through a rotating matrix that gets in contact alternatively with the two fluid streams and acts as a thermal accumulator. To increase the heat capacity and the overall exchange surface, the rotating matrix is filled by a series of folded metal sheets. In the paper we de-scribe a methodology to account for the effects of the Ljungström in a virtual test-rig implemented in a Computational Fluid Dynamics environment. To this aim, a numerical model based on the work of Molinari and Cantiano was derived and implemented in the OpenFOAM library. RANS numerical results were compared with those of a mono-dimensional tool used by ENEL to design Ljungström heat exchangers and validated against available measurements in a real configuration of a thermal power plant.